Experimental Characterization and Finite Element Investigation of SiO2 Nanoparticles Reinforced Dental Resin Composite - Jaleh, Babak; Kashfi, Mohammad; Mohazzab, Behnaz Feizi; Niaee, Morteza Shakhsi; Vafaee, Fariborz; Fakhri, Parisa; Golbedaghi, Reza; FAUSTO, RUI (Nature Portfolio, 2024)
In this study, a commercial dental resin was reinforced by SiO2 nanoparticles (NPs) with different concentrations to enhance its mechanical functionality. The material characterization and finite element analysis (FEA) have been performed to evaluate the mechanical properties. Wedge indentation and 3-point bending tests were conducted to assess the mechanical behavior of the prepared nanocomposites. The results revealed that the optimal content of NPs was achieved at 1% SiO2, resulting in a 35% increase in the indentation reaction force. Therefore, the sample containing 1% SiO2 NPs was considered for further tests. The morphology of selected sample was examined using field emission scanning electron microscopy (FE-SEM), revealing the homogeneous dispersion of SiO2 NPs with minimal agglomeration. X-ray diffraction (XRD) was employed to investigate the crystalline structure of the selected sample, indicating no change in the dental resin state upon adding SiO2 NPs. In the second part of the study, a novel approach called iterative FEA, supported by the experiment wedge indentation test, was used to determine the mechanical properties of the 1% SiO2-dental resin. Subsequently, the accurately determined material properties were assigned to a dental crown model to virtually investigate its behavior under oblique loading. The virtual test results demonstrated that most microcracks initiated from the top of the crown and extended through its thickness.
Keywords: Dental Resin; Finite Element Analysis; Mechanical Properties; Nanocomposite